The dovish turnaround: Germany's social benefit reform and job findings - Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
On the labour markets, recent decades were characterised by structural supply-side reforms in many countries. Following its hawkish reforms from the 2000s, Germany has recently made a dovish turnaround. Conditions in basic income support for unemployed became more generous. Before, a temporary moratorium on sanctions had been imposed, providing a unique policy shift. We analyse the short-run consequences for job findings, building on large administrative data and a novel control group approach. The moratorium dampened job findings by four percent and the subsequent benefit reform by almost six percent in the first year. Other factors played a still larger role for the recent weakening of job findings. – – Auf den Arbeitsmärkten waren die letzten Jahrzehnte in vielen Ländern von strukturellen Reformen auf der Angebotsseite gekennzeichnet. Nach den Hartz-Reformen in den 2000er Jahren hat Deutschland kürzlich eine Kehrtwende vollzogen. Die Bedingungen der Grundsicherung für Arbeitslose wurden großzügiger. Zuvor galt ein befristetes Sanktionsmoratorium. Wir analysieren die kurzfristigen Auswirkungen auf die Beschäftigungsaufnahmen und verwenden umfangreiche administrativer Daten sowie eine neue Kontrollgruppe. Das Moratorium dämpfte die Jobaufnahmen aus der Grundsicherung um vier Prozent und die nachfolgende Bürgergeldreform um fast sechs Prozent im ersten Jahr. Andere Faktoren spielten für die jüngste Abschwächung der Arbeitsaufnahmen eine noch größere Rolle.
Keywords: J64; J2; 330; Job Findings; Reforms; Sanctions; Social Benefits